Investigando o nível de stress entre estudantes do terceiro e quarto ano do curso de odontologia de uma instituição de ensino privado - Gabriel, Keila May (2005)
ABSTRACT When human being faces not desirable consequences after trespass physical and psychological body borders until reach an exhaustive condition completely, becomes able to choose the way will follow depending on the capacity to understand the difficulties of life. When he is not able to understand, he can face episodes of stress. The aim of this work was to verify the differences in the levels of stress in students of Odontology when they are doing their third and fourth year of studies, whose activity is meanly attending ambulatory patients of an university seated in a big city of the Paraná State, Brazil. A literature review was made to support theoretically this work and indeed, it was submitted to the groups a social demographic questionnaire and the LSS-/VAS A list of symptoms of stress. After all, it was made a statistical analysis. This analysis was made to evaluate the level of stress in students in a total sample of 166 subjects; to verify the general level of stress in students of Odontology during the years of 2003 and 2004; to compare the level of stress in students of third and fourth year; analyses the relation between total sample and specific groups with social demographic variables; to identify symptoms which have more and less frequency in total sample and subgroups; to verify which dimension (physiological, emotional, cognitive and social) concentrates the higher level of stress of the students, considering total sample and subgroups. The results pointed that there is no significant difference in the level of stress during the year of 2003, but there is a significant difference in the level of stress during the year of 2004, when some changes were made in the educational proceedings in the institution, specifically to the Odontology course. The third year students of 2004 presented higher levels of stress and the most significant was emotional and after that, cognitive. The emotion shall be dissociated to people s daily routine, but must be understood and worked individually and in groups, in order to develop actions which meet plausible solutions to situation of conflict, as being internal, as external. It is fundamental to study more deeply this subject to understand the stress in communities.